Driving Forces of Landscape Pattern Evolution due to Land Use Changes in the Kambang Iwak Kecik Catchment, Palembang - Muthmainah, Nyimas Atika Marwiyah; Putranto, Dinar Dwi Anugerah; Juliana, Imroatul Chalimah (Jurnal Teknik Sipil, 2025)
Rapid urban development in Palembang has significantly increased surface runoff due to reduced infiltration areas, raising flood risks in low-lying zones. The Kambang Iwak Kecik Retention Pond plays a critical role in capturing runoff from its surrounding catchment. This study identifies the contributing watershed areas and estimates flood discharges under design rainfall conditions. A GIS-based approach delineated seven sub-watersheds using Digital Elevation Model (DEM) data and flow direction analysis. Design rainfall intensities for return periods of 2"“50 years were derived from Gumbel and Log Pearson Type III distributions. Peak discharges, calculated using the Modified Rational Method, ranged from 0.04 to 0.38 m ³/s across sub-catchments. The total flood volume for a 10-year event exceeded the existing storage capacity of the retention pond, indicating a critical capacity deficit. These findings emphasize the importance of spatial-hydrological modelling in developing adaptive drainage strategies to enhance urban flood resilience.